Modern Approaches to Diagnostics and Correction of Aging Biomarkers - Ilmira R. Gilmutdinova; https://orcid.or 0001-6743-2615; Elena Yu. Kostromina; Maksim Yu. Yakovlev; Inessa Kh. Yafarova; Rinat G. Gilmutdinov; Irina A. Kaverina; Anton V. Ershov; Andrey N. Isaev; Alexey A. Moskalev (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
From the biomedicine point of, view ageing is a natural process, characterized by a gradual decrease in the physiological integrity and adaptive abilities of the body, leading to a violation of its functions and an increase in the risk of death with age. Demographic aging of the population is a serious socio-economic problem, both in Russia and around the world. The main cellular and molecular signs of aging include genome instability, telomere shortening, epigenetic alterations, impaired proteostasis, impaired nutrient recognition, mitochondrial dysfunction, cellular aging, the stem cell pool depletion and changes in intercellular interaction, extracellular matrix rigidity, as well as activation of retrotransposons and chronic inflammation. For these reasons, in modern healthcare, preventing premature aging and treating age-related diseases is becoming a priority task. This review presents modern approaches to the quantitative assessment of the aging process using aging biomarkers as functional parameters reflecting the biological organism age at the molecular, cellular, and organismal levels. This work also considers the actual non-drug and drug interventions allowing to slow down the development of age-associated pathological processes, allowing you to increase the quality and duration of life.